Strategi Komunikasi Pemasaran di Era Pandemi Covid-19 - Feky Reken; Siska Jeanete Saununu; Nur Ariyandani (Univiversitas Dr. Djar Wattiheluw, 2023)
Marketing communication strategy plays an important role in the sustainability of the company. Through marketing communication strategies, companies can provide information and influence consumers so that purchases can occur, which will bring income to the company. This study aims to describe the marketing communication strategy implemented by CitraLand Tallasa City Makassar in the era of the COVID-19 pandemic based on analysis using the marketing communication mix. Data for this descriptive qualitative study were gathered through interviews with related parties, specifically the designers and implementers of marketing communication strategies at CitraLand Tallasa City Makassar, as well as through observations. The results of the study show that CitraLand Tallasa City Makassar made some adjustments to its marketing communication strategy during the COVID-19 pandemic. The adjustments focus on carrying out a marketing communication strategy by utilizing digital media.